First person - Yuka Kobayashi (The Company of Biologists, 2021)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Yuka Kobayashi is first author on ' Early manifestations and differential gene expression associated with photoreceptor degeneration in Prom1-deficient retina', published in DMM. Yuka is assistant professor in the lab of Prof. Kazuhiro Kimura at Yamaguchi University Graduate School of Medicine, Ube, Japan, investigating ophthalmology.